Comparative Treatment Outcomes of Pre and Post-exercise TENS Application on Knee Osteoarthritis: A Preliminary Report - Bello, A.I.; Crankson, S.; Adegoke, B.O.A. (Rehabilitation Process and Outcome, 2014)
OBJECTIVE: The effects of TENS before exercise (TBE) and TENS after exercise (TAE) in the management of knee osteoarthritis (OA) were compared. METHODS: Fifteen participants with knee OA were alternatively assigned to either TBE or TAE groups. Participants’ pain, active knee flexibility, thigh girth, disability, and activity levels were assessed at baseline and at the end of eight-week study. Mixed design two-way analysis of variance (ANOVA) at P  0.05 was used to compare the two groups. RESULTS: The mean age of the participants was 58.1 ± 10.9 years. Post-intervention comparison showed that TAE had significantly lower scores (1.9 ± 0.9) than TBE (4.3 ± 1.5) on Disability Index Questionnaire (DIQ) (F-ratio = 10.5; P = 0.006), and significantly lower scores (0.8 ± 0.3) than TBE (1.4 ± 0.6) on Patient Assessment Scale (PAS) (F-ratio = 8.3; P = 0.013). However, both groups did not significantly differ on the selected impairment measures. CONCLUSION: TAE was found to be more effective on the primary outcome measures in patients with knee OA.
Research Article
Keywords: Osteoarthritis; Exercise; TENS